CORRELATION BETWEEN MATERNAL EDUCATION AND EMPLOYMENT STATUS WITH EXCLUSIVE BREASTFEEDING HISTORY - Setiyarini, Anggraini Dyah; Andini, Dwi Margareta (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: In 2022, the sole lactation coverage rate in Indonesia was recorded at 67.96%. According to the East Java Provincial Health Office, 67.54% of women in the province of East Java were exclusively nursing in 2022. This falls very short of the 80% goal set by the Republic of Indonesia's Ministry of Health in 2020. Infants require breast milk and adequate nutrition to increase their nutrient levels during growth. Exclusive breastfeeding cannot be optimally provided due to various factors such as maternal education history, which influences the mother's limited knowledge about the importance of exclusive breastfeeding maternal employment. These two factors affect the provision of exclusive breastfeeding to infants. Given the foregoing context, the study's goal was to discover how a mother's job description affected her history of exclusive breastfeeding. Method: The study employed a cross-sectional strategy and a quantitative, analytical observational design. Purposive sampling was used to choose 111 participants for the study, who were all mothers with infants between the ages of 6 and 12 months. The study will be carried out in Madiun City's Public health Service Tawangrejo East Java, Indonesia. operational region. This study was conducted from February to April 2024. Data collection utilizes questionnaires. The chi-square test was used to analyze the data. Result: The p-value is 0.03 or less than 0.05, showing that the history of exclusive breastfeeding was significantly correlated with the mother's employment position and educational attainment. Mothers with a history of exclusive breastfeeding have a poor association between their employment status and education, as indicated by their correlation coefficient (R) value of 0.362. Conclusion : there is a relationship between education, employment level, and history of exclusive breastfeeding at the Tawangrejo Community Health Center in Madiun, East Java, Indonesia.